QM Study on the Mechanism of Carbonic Anhydrase II Inhibition with Glycosylcoumarin as Non-Zinc Mediated Inhibitors from Thermodynamic View Point - Ghiasi, Mina; Seifi, Mina (Journal of Nutritional Therapeutics, 2021)
Carbonic anhydrase is an enzyme which has the zinc as the metallic part of it. This enzyme catalyzes the reversible reaction of turning carbon dioxide into bicarbonate. In this research the mechanism of inhibition a new class of inhibitor of this enzyme, glycosyl coumarin has been modeled using the density functional theory (DFT). First, the most constant confirmer of this four coumarin sugar derivatives which includes galactose, mannose, ribose and glucose has been selected and then they had been interacted as inhibitor with CA (II) enzyme’s active site. In further for showing the effect of sugar in these molecules, coumarin itself had been chosen as inhibitor and the inhibitory effect is surveyed. All calculations have been done by density functional theory in level of B3LYP with basic set 6-31G* and with Minnesota function M06 with basic set 6-31+G*. Thermodynamic functions like enthalpy of formation, entropy of formation and Gibbs free energy for CA-inhibitor have been computed. The results indicate that the reaction among these groups of inhibitors and Carbonic anhydrase is not of the type of direct and syndetic but the enzyme is deactivated with space effect and addition to this, the computed thermodynamic functions show that although this coumarin sugar derives have deterrence in the range of micro molar but, coumarin without sugar is a stronger deterrence for CA II. Finally, the interaction between the most constant confirmer (galactose coumarin) is surveyed as the best deterrence using the explicit solvent method.